Implementation Of Erp-Based Open Source Odoo For Chicken Farm Procurement And Sales Operation Management System Using The Quickstart Method (Studi Case: Cv. Cindil Laras) - Yuliano, Edward; Budiono, Avon; Puspitasari , Warih (eProceedings of Engineering, 2024)
Development in the era of globalization is very dependent onthe economic sector as a measure of success carried out by thegovernment. The role of the community in national development,especially in economic development, is Micro, Small and MediumEnterprises (MSMEs). The position of MSMEs in the nationaleconomy has an important and strategic role. This condition isvery possible because the existence of MSMEs is quite dominantin the Indonesian economy.With the high number of needs that must be met, severalchallenges arise in the production process, namely monitoring,maintenance management. On CV. Cindil Laras maintenancemanagement monitoring process can be said to be stillconventional, resulting in a decrease in maintenancemanagement. This research aims to develop an integrated ERPsystem using Odoo open-source software developed using theQuickStart method. QuickStart is an application developmentmethod suitable for implementation in MSMEs which has threestages in it, namely kick-off call, configuration and analysis. Thesystem developed will be able to integrate existing businessprocesses on CV. Cindil Laras can efficiently help in monitoringcompany data related to procurement and sales which can helpcompany decision making and also to support the procurementand sales process. Keyword— Enterprise Resource Planning (ERP),Procurement, Sales, QuickStart, Odoo